The length of the ski track and the velocity of top world cup slalom skiers - Zvan, M.; Lesnik, B. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: In this study, we aimed 1.) to establish the differences in the choice of the line of skiing between individual competitors in the World Cup and to determine the distance of their lines of skiing from the pole (fall line), and 2.) to establish whether the competitors with a shorter line of skiing in the pole setting achieve higher velocities, and consequently, faster sliding among the slalom gates, and finally a better result.